Long-term clinically relevant rodent model of methotrexate-induced cognitive impairment. Issue 8 (2nd April 2020) - Berlin, Connor; Lange, Katharine; Lekaye, H Carl; Hopland, Kelsey; Phillips, Samantha; Piao, Jinghua; Tabar, Viviane
Abstract: Background: With the enhanced use of chemotherapy and the advent of increased patient survival rates, there are an increasing number of cancer survivors living with chemotherapy-induced cognitive impairment. A growing number of clinical studies have brought to light the association of agents like methotrexate in generating these neurological sequelae, although mechanisms remain unclear. Methods: Here, we use a clinically relevant regimen of several cycles of methotrexate and leucovorin rescue to develop a model of chemotherapy-induced cognitive impairment, and investigate the in vivo long-term (16 mo) impact of high-dose systemic methotrexate on white matter cellular dynamics as assessed by stereology, animal behavior, and diffusion tensor imaging. Results: Our results indicate that at 6 and 16 months post-chemotherapy, methotrexate-treated rats exhibit a significant and permanent decrease in the number of oligodendrocytes and their progenitors in the white matter, in corpus callosum volumes, and myelin basic protein. These findings are associated with mostly delayed deficits in performance on Morris Water Maze and Novel Object Recognition tasks. Diffusion tensor imaging demonstrates significantly decreased fractional anisotropy values in the callosum genu, body, and splenium, as well as previously unassessed areas like the fimbria. Interestingly, these white matter changes are preceded by an earlier, transient decrement in white matter microglia at 3 months, and hippocampal neural progenitors at 3 and 6 months. Conclusion: These results demonstrate a significant negative impact of methotrexate on the oligodendrocyte compartment and white matter, associated with cognitive impairment. The data also support the use of diffusion tensor imaging in monitoring white matter integrity in this context.